A Study On The Generation Rate Of Food Waste And Its Treatment Using Autoclave - Ibrahim, Nurazim (2012)
Malaysian municipal solid waste (MSW) stream consist of 50 to 60 % of food waste. Nature or characteristics of food waste causes it hard to be managed and whilst cause many environmental problems. Dumping food wastes to the landfill take up a large space area and reducing the lifespan of landfill. Until March 2012, the total number of landfill recorded was 296 sites but the number of sites that are still actively in operation was only 166, while 130 sites were closed. Food waste generation study was carried out in Universiti Sains Malaysia (USM) engineering campus to estimate the generation rate and food waste fractions, addressing factors that influence food waste generation, and determine characteristics of food waste before and after autoclaving treatment to identify suitability of wet heating treatment as alternative management system.